2020
DOI: 10.1021/acs.est.9b06701
|View full text |Cite
|
Sign up to set email alerts
|

Titania–Samarium–Manganese Composite Oxide for the Low-Temperature Selective Catalytic Reduction of NO with NH3

Abstract: A novel Ti-doped Sm–Mn mixed oxide (TiSmMnO x ) was first designed for the selective catalytic reduction (SCR) of NO x with NH3 at a low temperature. The TiSmMnO x catalyst exhibited a superior catalytic performance, in which NO x conversion higher than 80% and N2 selectivity above 90% could be achieved in a wide-operating temperature window (60–225 °C). Specially, the catalyst also showed high durability against the large space velocity and excellent SO2/H2O resistance. Ti incorporation can efficiently inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…These results suggested that the intrinsic properties governing the direct oxidation of NO were different from that of NH 3 oxidation. Combined with the results listed in Table 4, it can be deduced that surface oxygen plays a crucial role in NO oxidation to NO 2 over the Fe-M catalysts [6,57,58].…”
Section: Direct Oxidation Of Nh 3 and Nomentioning
confidence: 70%
See 1 more Smart Citation
“…These results suggested that the intrinsic properties governing the direct oxidation of NO were different from that of NH 3 oxidation. Combined with the results listed in Table 4, it can be deduced that surface oxygen plays a crucial role in NO oxidation to NO 2 over the Fe-M catalysts [6,57,58].…”
Section: Direct Oxidation Of Nh 3 and Nomentioning
confidence: 70%
“…For metal oxide NH 3 -SCR catalysts, generally, surface oxygen (O α ) is important for the oxidation of NO to NO 2 , thus promoting the "fast-SCR" reaction at low-temperature [6,57,58]. In addition, the over-oxidation of NH 3 accounted for the decreased NO x conversion at high temperatures [1,13,16,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The promotion by the redox properties will cause the operational temperature window shifting to lower temperatures, and the increase in acidity facilitates the NH 3 adsorption at high temperatures. 49,64 Hence, tuning the redox properties and acidity is an efficient strategy to achieve high activity. Doping has been widely applied in catalyst design because it significantly affects the chemical state and structure of the catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…The NO 2 contributed to the low temperature NH 3 -SCR via a "fast-SCR reaction" (NO + NO 2 + NH 3 → 2N 2 + 3H 2 O). 49 Hence, NO oxidation and NH 3 oxidation were investigated and the results are shown in Fig. 7 and S3 (ESI †).…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Compared with single MnO x catalysts, Sm-Mn composite catalysts exhibited superior N 2 selectivity. 67,68 Plenty of studies had shown that the reaction after Sm doping mainly proceeded via the E-R mechanism, in which -NH 2 was the key intermediate. There was a large electronegativity difference between Sm 2+ and Mn 4+ , and Sm 2+ would preferentially lose electrons.…”
Section: Composite Manganese Oxide-based Catalystsmentioning
confidence: 99%